Nurses Attitude Toward Patients as A Translating of Nursing Code of Ethics in Universitas Hasanuddin Hospital - Ismayani Safitri; Hapsah Hapsah; Akbar Harisa (Faculty of Nursing, Universitas Hasanuddin, 2020)
Introduction: The nursing code ethics is a guideline and framework of nurses during delivering nursing care services include making clinical decisions. The Indonesian Nursing Code of Ethics contains 5 principles of nurse's responsibilities such as responsibility to clients’ care. The aim of this study to describe the attitude of nurses towards clients at Hasanuddin University Hospital Makassar as a part of nursing code of ethic translation. Method: This research applied a quantitative study with descriptive survey. There are 95 nurses recruited as respondents through purposive sampling methods. Results: There are 80% of respondents have excellent rate while rest of nurses who have good rate in attitude towards the clients in order to translate the nursing code ethics into clinical practice. Conclusion: The majority of nurses already implemented the nursing code ethics, particularly Indonesian version, into clinical practice. However, examining the whole principles of the ethic codes is still needed in order to improve nursing care quality in hospital setting.